Peran UMKM (Usaha Mikro Kecil Menengah) Dalam Meningkatkan Kesejahteraan Masyarakat - Kadeni, Ninik Srijani (Universitas PGRI Madiun, 2020)
The purpose of this literature study discussion is to illustrate the role of MSMEs (micro small and medium enterprises) in improving the welfare of the community. To discuss this problem using the literature study method. The results of the discussion show that the role of micro, small and medium enterprises is very important to improve the community's economy. This business was chosen because it has been proven tested in dealing with any situation including the monetary crisis and its major role in equalizing income and the welfare of the community